Gradual Versus Abrupt Smoking Cessation: A Randomized, Controlled Noninferiority Trial - Lindson-Hawley, N; Banting, M; West, R; Michie, S; Shinkins, B; Aveyard, P (American College of Physicians, 2016)
Background: Most smoking cessation guidelines advise quitting abruptly. However, many quit attempts involve gradual cessation. If gradual cessation is as successful, smokers can be advised to quit either way. Objective: To examine the success of quitting smoking by gradual compared with abrupt quitting. Design: Randomized, controlled noninferiority trial. (International Standardized Randomized Controlled Trial Number Register: ISRCTN22526020) Setting: Primary care clinics in England. Participants: 697 adult smokers with tobacco addiction. Intervention: Participants quit smoking abruptly or reduced smoking gradually by 75% in the 2 weeks before quitting. Both groups received behavioral support from nurses and used nicotine replacement before and after quit day. Measurements: The primary outcome measure was prolonged validated abstinence from smoking 4 weeks after quit day. The secondary outcome was prolonged, validated, 6-month abstinence. Results: At 4 weeks, 39.2% (95% CI, 34.0% to 44.4%) of the participants in the gradual-cessation group were abstinent compared with 49.0% (CI, 43.8% to 54.2%) in the abrupt-cessation group (relative risk, 0.80 [CI, 0.66 to 0.93]). At 6 months, 15.5% (CI, 12.0% to 19.7%) of the participants in the gradual-cessation group were abstinent compared with 22.0% (CI, 18.0% to 26.6%) in the abrupt-cessation group (relative risk, 0.71 [CI, 0.46 to 0.91]). Participants who preferred gradual cessation were significantly less likely to be abstinent at 4 weeks than those who preferred abrupt cessation (38.3% vs 52.2%; P = 0.007). Limitations: Blinding was impossible. Most participants were white. Conclusion: Quitting smoking abruptly is more likely to lead to lasting abstinence than cutting down first, even for smokers who initially prefer to quit by gradual reduction.